Laboratory investigation on the condensation and corrosion rates of top of line corrosion in carbon steel: a case study from pipeline transporting wet gas in elevated temperature - Rozi, F. (Taylor and Francis Ltd., 2018)
A glass cell was designed to simulate the condition for top of line corrosion encountered in wet gas transportation pipelines. Aqueous solution of 3 wt- NaCl saturated with CO2 at atmospheric pressure was employed. Effect of temperature gradient in the formation of condensation and its rate was investigated. API 5L Grade X65 carbon steel material was used as the working electrode for the experiment. The condensation rate was measured for the temperature gradient of 20Â°C, 30Â°C and 50Â°C under atmospheric condition for 24â h duration of the experiment. The corrosion rate of the specimens was measured using weight loss and Linear Polarisation Resistance (LPR) techniques. The LPR probe was immersed in the collected condensed water from the experiment to calculate the corrosion rate. The measured corrosion rate from the weight loss technique was in agreement with the corrosion rate measured from LPR. The corrosion rate measurement was repeated with the addition of 1000â ppm of pH modifying agent. This study indicates that the corrosion rate of pipeline and piping when subject to temperature gradient of 50Â°C and above is very high and alarming. Â© 2018 Institute of Materials, Minerals and Mining Published by Taylor & Francis on behalf of the Institute